Development of Equivalent Circuit Models for Non-Linear Resistors - Solis, Romeo G. (Philippine Engineering Journal; Vol 11 No 2 (1990), 2021)
The modeling of non-linear devices confront both users and developers of computer-aided design programs. This paper shows how large-signal models for voltage and current controlled resistors can be developed based on the piecewise-linear characteristics of the device. For both voltage controlled and current controlled non-linear resistors, two models are developed. One model is Foster-like in the sense that the sub-circuits are connected either in series or parallel to form the model. The other model is Cauer-like in the sense that the topology is of ladder type. Methods for developing the models are presented.